Monolithic roof glazing for motor vehicle
By adopting a single-piece assembly glass design in automotive glass, using a silver layer stack and a polymer compound layer that reflects infrared radiation, the problem of automotive glass in the prior art is solved between preventing excessive heating and providing sufficient lighting, and the problem of automotive glass in the prior art is achieved. The combination of low TTS and TL simplifies the manufacturing process and reduces costs.
Patent Information
- Application Number
- CN202380040932.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-16
- Filing Date
- 2023-05-11
- Publication Date
- 2025-01-03
AI Technical Summary
Existing automotive assembly glass is difficult to find the best tradeoff between preventing overheating and providing adequate lighting, and is complex and costly, especially when using laminated structures, resulting in total transmissive solar energy (TTS) and light transmittance (TL). ) adjustment is difficult to achieve, and it increases vehicle weight and fuel consumption.
Using a single-piece assembly glass design, including transparent glass sheets, silver layer stacks that reflect infrared radiation and polymer compound layers, the latter containing colorants to absorb visible light and be transparent to infrared radiation, improving manufacturing simplicity and reducing cost.
The combination of low TTS and TL is achieved, reducing emissivity, improving sunlight control performance, simplifying the manufacturing process, and reducing manufacturing costs while maintaining visual comfort and stability of internal temperature.
Smart Images

Figure CN119255973A_ABST
Abstract
Description
[0001] The invention relates to an assembled glass for automobiles, in particular to an assembled glass used as an automobile glass roof.
[0002] Glazing used as a panoramic roof or fixed roof in a vehicle must comply with a certain number of standards with regard to heating of the vehicle interior when exposed to strong sunlight:
[0003] - on the one hand, not allowing all incident solar radiation to pass, so as not to overheat the vehicle interior and / or to limit energy consumption (e.g. excessive use of air conditioning due to the amount of heat entering the cabin), and
[0004] - On the other hand, let in a large enough amount of light to fully illuminate the interior space and ensure a minimum external visibility to maintain visual comfort and a cozy feeling.
[0005] Meeting these two requirements - namely preventing excessive radiation from entering and providing sufficient lighting for the interior space - is necessarily a compromise. Therefore, there is a need for glass that provides the best compromise in terms of heat reflection while maintaining a certain light transmission.
[0006] Furthermore, reducing CO2 emissions is a major challenge for industry today. For example, in the context of CO2 energy conservation, the US Federal Regulations (CFR, https: / / www.law.cornell.edu / cfr / text / 40 / 86.1869-12) grant CO2 credits to automakers in NAFTA markets for non-recycled CO2 reduction technologies, particularly involving IR reflective coatings or heat absorbing glass. For example, panoramic sunroof glazing has an outer surface that is highly exposed to direct sunlight, which would result in heat and glare if the glass were not coated or tinted.
[0007] The initial technical purpose of the invention is to limit glare by reducing light transmission through the glass and also to improve solar protection in automotive glazings, and in particular those used as roofs, thereby avoiding heating of the interior space of the passenger cabin.
[0008] To assess the heat transfer through glazing, the total solar transmittance (TTS) is usually measured using convention "A" AM 1.5 according to ISO 13837. Solar protection is therefore measured by the total transmitted solar energy (TTS) of this type of glazing.
[0009] To assess the light transmission through the glazing in the visible range (380-780 nm), the T L Light transmittance.
[0010] T LIt can be reduced by absorption. According to current technology, absorption is achieved by using body-tinted glass sheets in the glazing or, alternatively or additionally, by using one or more tinted PVB layers in laminated glazing (i.e. glazing made of several glass sheets joined together). However, such designs lead to overheating of the glazing.
[0011] Another important factor regarding solar control glazing and its ability to prevent internal heating is its ability to selectively reflect the sun's infrared rays. Typically, this ability is achieved by stacking thin layers (i.e. with a thickness of the order of a few nanometers or tens of nanometers), one of which has a high reflectivity in the thermal infrared. This ability is typically achieved by a stack comprising at least one and preferably two or even three silver layers a few nanometers thick, in particular of the type described in applications WO 2005 / 051858 or WO 2013 / 104439, to which reference is made for further details of such stacks.
[0012] A glazing unit equipped with such a stack can be characterized, for example, by its total emissivity at normal incidence, ε , measured, for example, in accordance with standard NF EN 12898 (2001). n , to measure the ability to reflect infrared radiation. Emissivity ε n The lower it is, the more infrared light is reflected by the glazing.
[0013] To meet the above objectives, several configurations of laminate structures have been described.
[0014] According to a first possibility, it is known from publication WO 2006 / 108980 A2 to use tinted lenses which absorb part of the radiation and filter out a large part of the incident radiation spectrum, without distinguishing between the different parts of the solar spectrum (UV-visible-near IR).
[0015] According to another possible construction, it has been proposed to use a colored interlayer, in particular a colored PVB (polyvinyl butyral) sheet, bonding two glass sheets (optionally also colored). For an example of such a construction, see also publication EP0687554A1.
[0016] The specification of patent US Pat. No. 6,910,729 instead describes a thermal comfort glazing system combining electrochromic glass with a low-e coating on the surface facing the interior of the vehicle.
[0017] In another solution, EP 1 060 876 A2 describes a laminated glazing unit comprising an outer glass sheet, a sun protection stack comprising two silver layers arranged on face 2 (the face numbered from the outside inwards), a sheet of transparent PVB, a sheet of tinted PVB, and an inner glass sheet on which a low-e layer of fluorine-doped tin oxide is deposited.
[0018] Various combinations of the above systems (PVB and / or tinted glass) have also been proposed. This usually results in a final T L The value is 8-20% and the TTS factor is 20-35%.
[0019] Although such values are generally satisfactory, the solutions proposed so far are expensive and complex to implement and the price of the final glazing is relatively high, in particular due to the high cost of body-tinted glass and / or body-tinted PVB (or other interlayers). Body tinting refers to the introduction of a dye during the manufacturing phase of the product (glass or PVB) so as to be evenly distributed throughout the entire volume of said product, in contrast to clear glass or clear PVB which do not contain such dye.
[0020] However, as mentioned above, current solutions appear to be relatively expensive and complex to implement, leading to a joint reduction of TTS and TL without any possible adjustment, especially by using tinted glass and / or tinted PVB films in laminated glazing. However, this cannot be achieved without a corresponding increase in the emissivity of the glazing.
[0021] Furthermore, all the above configurations involve laminated glazing, i.e. glazing comprising at least two glass sheets. Even with today's technology, the production of such glazing is costly and quite complex. It also increases the overall weight of the vehicle (thermal or electrical) and therefore its fuel consumption.
[0022] In order to obtain an optimal TL / TTS / emissivity compromise, glazings are sought that have an equally effective absorption profile, but whose manufacturing is much less complex than those of the prior art and that are based in particular on simple (or monolithic) glazings, i.e. comprising only one glass substrate (glass sheet). Providing such a single glazing is the object of the present invention.
[0023] In particular, according to the present invention, preferably glazing units are sought which have the following specifications in common:
[0024] - TTS of around 20% or less,
[0025] - T less than 10% or even less than 5%, and ideally about 1 to 2% L Light transmittance,
[0026] - Lowest possible emissivity ε n , and in particular an emissivity ε less than or equal to 30% n .
[0027] The problem behind the present invention is therefore to provide a glazing which is easy and economical to manufacture, in particular a glazing which does not comprise body-tinted glass or body-tinted PVB, which can in particular be used as a vehicle roof, which satisfies the desired compromise between TTS and TL, in particular a visible light transmission T of less than 10% or even less than 5%. L , and a TTS factor of less than 20%, and a low emissivity, which is in particular less than or equal to 30%.
[0028] More particularly, the above-mentioned technical problem is solved with the monolithic glazing according to the invention.
[0029] In the building industry, monolithic glazing is traditionally defined as glazing comprising a single sheet of glass (see, for example, "Le dictionnaire professionnel du BTP" published by Eyrolles).
[0030] This type of glazing has the following characteristics: It consists of a single transparent glass sheet as a support and protective elements. It consists of the following elements from the outside to the inside of the glazing:
[0031] - the transparent glass sheet,
[0032] a multilayer of layers reflecting infrared radiation, in particular starting from 780 nm and preferably into the far infrared (3 to 50 micrometers), said multilayer preferably being in contact with the inner surface of said transparent glass sheet,
[0033] - a layer of a polymer compound, preferably deposited directly on the stack of said layers or bonded thereto via a layer of adhesion promoter, said polymer compound comprising a colorant absorbing light in the visible range from 380 to 780 nm and being substantially transparent to infrared radiation, in particular to infrared radiation in the wavelength range from 780 to 2000 nm, said layer being in contact with the external environment (i.e. it is the last element in the series, no glazing sheet, layer or stack covering it). The terms "external" and "internal" refer to the positioning of the glazing in the vehicle in which it is equipped.
[0034] According to the invention, the outer surface of the glass sheet is at least partially exposed (ie in direct contact with the air outside the vehicle).
[0035] Additional advantageous features of such glazings are given below, which can of course be combined with one another if desired:
[0036] - the dye exhibits an absorption spectrum between 380 and 2000 nm for a 40 micron layer in an acrylate polymer and at a concentration of 1% by weight, as measured by a Perkin-Elmer Lambda 950 spectrophotometer at 25°C, the absorbance averaged between 780 nm and 2000 nm being at most one third, and preferably at most one fifth, or even at most one seventh, of the absorbance averaged between 380 nm and 780 nm.
[0037] - The dye is black or substantially black.
[0038] - At 25°C, the average molar extinction coefficient (or molar absorbance) of the dye between 780 nm and 2000 nm is at most one third, and preferably at most one fifth, of the average molar extinction coefficient between 380 nm and 780 nm.
[0039] It is well known that the molar extinction coefficient, also called molar absorptivity or molar absorptivity, characterizes the ability of a composition to absorb light. The Beer-Lambert law states that it does not depend on the concentration of the composition or the thickness through which the light passes, but rather on the nature of the solute (in this case the dye) and the solvent (in this case the matrix), the wavelength of the incident light, and the temperature. For the purposes of the present invention, the "average" molar extinction coefficient thus corresponds to the average value of said coefficient measured over the wavelength range considered.
[0040] The stack of infrared radiation reflecting layers is a stack comprising at least two functional layers based on silver, preferably at least 3 functional layers based on silver, separated by layers of dielectric material, in particular oxide or nitride.
[0041] The polymer layer comprises or preferably consists of a polymeric compound selected from (meth)acrylate compounds, which are preferably multifunctional and comprise at least two acrylate functional groups.
[0042] The polymer layer is obtained by crosslinking a polymerizable composition comprising a (meth)acrylate compound optionally containing a polyorganosiloxane group, a polymerization initiator and optionally an adhesion promoter, wherein the (meth)acrylate compound comprises a high-functionality (meth)acrylate compound:
[0043] - has at least four (meth)acrylate functional groups and represents, in increasing order of preference, at least 65%, at least 70%, at least 80%, at least 90%, at least 94% by weight relative to the total weight of the composition, or
[0044] - has at least five (meth)acrylate functional groups and represents, in increasing order of preference, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight of the composition relative to the total weight of the composition.
[0045] - Preferably, the polymerizable composition comprises a high functionality (meth)acrylate compound having at least six (meth)acrylate functional groups and constituting, in increasing order of preference, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% of the composition.
[0046] The term "(meth)acrylate" is understood to mean either acrylate or methacrylate.
[0047] A (meth)acrylate function is understood to mean an acrylate function (CH2=CH-COO-) or a methacrylate function (CH2=CH(CH3)-COO-).
[0048] The polymer matrix is essentially of organic nature. It is obtained from the polymerizable composition. It results from the crosslinking of the polymerizable organic compounds present in the polymerizable composition.
[0049] The (meth)acrylate compounds account by weight in increasing order of preference relative to the total weight of the polymer layer:
[0050] - at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95% and / or
[0051] - up to 99%, up to 98%, up to 97%, up to 96%, up to 95%.
[0052] The (meth)acrylate compound has a molecular weight or average molecular weight (hereinafter referred to as molecular weight) of 150 to 10,000 g / mol.
[0053] The (meth)acrylate compounds include high-functionality (meth)acrylate compounds. These high-functionality compounds are selected from esters of acrylic acid or methacrylic acid, which contain at least four, at least five or at least six (meth)acrylate functional groups in increasing order of preference.
[0054] The (meth)acrylate compound including the high-functionality (meth)acrylate compound has a molecular weight of 500 to 10,000, 800 to 5,000, 1,000 to 2,000 g / mol in increasing order of preference.
[0055] In an advantageous embodiment, the high-functionality (meth)acrylate compound has at least four (meth)acrylate functional groups, which constitute in increasing order of preference at least 65%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight relative to the total weight of the polymer layer.
[0056] According to another advantageous embodiment, the high-functionality (meth)acrylate compound having at least five (meth)acrylate functional groups accounts for at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight, relative to the total weight of the polymer layer, in increasing order of preference.
[0057] According to a further advantageous embodiment, the high-functionality (meth)acrylate compound having at least six (meth)acrylate functional groups accounts for at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight, relative to the total weight of the polymer layer, in increasing order of preference.
[0058] Advantageously, the (meth)acrylate compound a) comprises a high functionality (meth)acrylate compound having at least six (meth)acrylate functional groups and a molecular weight of 1000 to 2000 g / mol. An example is CN9010EU, a product sold by Sartomer, which is an aliphatic urethane-acrylate prepolymer having six (meth)acrylate functional groups and a molecular weight of 1450 g / mol.
[0059] According to an advantageous embodiment of the invention, the polymerizable composition also has the following characteristics:
[0060] - it comprises at least one polymerization initiator, preferably a photoinitiator,
[0061] - the polymerization initiator accounts for 0.1 to 20% by weight, or 1 to 15% by weight, preferably 3 to 10% by weight and better still 4 to 8% by weight of the composition,
[0062] - the (meth)acrylate compound a) is selected from monomers, oligomers, prepolymers or polymers comprising at least one (meth)acrylate functional group,
[0063] - the (meth)acrylate compound is selected from esters of acrylic acid or methacrylic acid containing at least two (meth)acrylate functional groups,
[0064] - the (meth)acrylate compound optionally comprises at least one aliphatic urethane-acrylic oligomer,
[0065] - the (meth)acrylate compound comprises at least one oligomeric or prepolymerized monomer which contains, in increasing order of preference, at least 2, at least 3, at least 4, at least 5 or at least 6 (meth)acrylate functional groups,
[0066] the polymerizable composition may additionally comprise at least one additive selected from adhesion promoters, plasticizers, absorbers, release agents, heat and / or light stabilizers, thickeners, or surface modifiers,
[0067] The sum of all additives is from 0 to 10% by weight, preferably from 0 to 5% by weight, or even from 0.5 to 2.5% by weight of the composition.
[0068] According to one advantageous embodiment, the polymerizable composition comprises at least one additional compound comprising a polyorganosiloxane group and at least two (meth)acrylate functional groups.
[0069] According to the present invention, polymerization initiators and compounds comprising polyorganosiloxane groups are not considered to be additives.
[0070] The additional compound containing polyorganosiloxane groups has, for example, a molecular weight of 500 to 10,000 g / mol. Advantageously, the additional compound has, in increasing order of preference, a molecular weight of 500 to 15,000, 1,000 to 10,000, 3,000 to 7,000 g / mol. The molecular weight can be determined by gel permeation chromatography.
[0071] The additional compound comprises 0.05 to 5 weight percent of the polymerizable composition.
[0072] The compound containing polyorganosiloxane groups accounts for 0.05 to 5%, 0.1 to 4%, 0.2 to 3%, 0.3 to 2%, 0.3 to 1.5% of the total weight of the organic protective layer in increasing order of preference.
[0073] The polyorganosiloxane group of the compound containing a polyorganosiloxane group consists of 2 to 1000 organosiloxane units. The polyorganosiloxane group may be part of the main chain of the compound or part of a side chain.
[0074] The compound containing polyorganosiloxane groups can be selected from modified polyorganosiloxanes containing multiple (meth)acrylate functional groups. This type of compound corresponds to a compound having at least two (meth)acrylate functional groups, which are introduced at any position of the polyorganosiloxane chain (or backbone), in particular on a side chain or at the end of the main chain. In this case, the compound containing polyorganosiloxane groups accounts for 0.05 to 1.5% by weight, 0.1 to 1% by weight, 0.2 to 0.7% by weight, 0.4 to 0.6% by weight of the composition in an increasingly preferred order. This type of compound is sold, for example, under the name Byk 3505.
[0075] The compound containing polyorganosiloxane groups can be selected from modified poly(meth)acrylates containing polyorganosiloxane groups and at least two (meth)acrylate functional groups. This type of compound is sold, for example, by Sartomer under the name CN9800 ("bifunctional aliphatic acrylate silicone oligomer"). In this case, the compound containing polyorganosiloxane groups accounts for 0.2 to 4% by weight, 0.4 to 3% by weight, 0.6 to 2% by weight, 0.9 to 1.6% by weight of the composition in an increasing order of preference.
[0076] The thickness of the polymer layer is from 0.1 to 25 micrometers, preferably from 0.1 to 20 micrometers, even more preferably from 0.2 to 10 micrometers, even from 0.2 to 5 micrometers and very preferably from 0.5 to 3 micrometers.
[0077] - Colorant selected from Epolight sold by Epolin Compounds in the series, in particular compounds 7527B and Epolight 7527C.
[0078] -Colorant selected from Sudan Black ((2,2-dimethyl-1,3-dihydroperylene-6-yl)-(4-phenylazo-1-naphthyl)diazepine, C 29 H 24 N6, CAS 4197-25-5) or Nigrosine Solvent Black 5 (NigrosineSolvent black 5) (CAS 11099-03-9), and preferably Sudan Black
[0079] - The colorant represents 5 to 70% by weight of the polymer, preferably 10 to 60% by weight of the polymer and more preferably 20 to 50% by weight of the polymer.
[0080] The glass sheet has a thickness of 0.7 mm to 5 mm, preferably 1.6 mm to 3.1 mm.
[0081] A layer stack is a thin-film system with a thickness of 0.5 to 100 nm which comprises one or more silver-based layers, preferably at least two silver-based layers.
[0082] The invention also relates to the use of a monolithic glazing as described above as a roof, side window or rear window of a motor vehicle.
[0083] The invention also relates to a method for manufacturing a monolithic glazing unit as described above, comprising a single glass sheet, said method being characterized in that it comprises the following steps:
[0084] - depositing on the inner surface of the glass sheet a multilayer of layers reflecting infrared radiation, in particular infrared radiation having a wavelength greater than 780 nm,
[0085] - depositing on said stack a polymer layer comprising a colorant as described above, said colorant substantially absorbing light in the visible range and being transparent to infrared radiation,
[0086] - Drying and / or curing of the polymer layer containing the colorant, in particular by UV treatment.
[0087] By way of non-limiting example and for a better understanding of the present invention, the following Figure 1 A cross-sectional view of a glazing unit according to the invention is shown.
[0088] This design is particularly suitable for producing glass roof structures for automobiles, but can also be used as rear windows or even as side window glazing.
[0089] The glazing 10 according to the invention comprises a transparent glass sheet 1, i.e. its bulk is not tinted. In particular, such glazing is usually obtained using a float glass process. In particular, such untinted glass may have a T of at least 88%, and more typically about 90%. L Light transmittance.
[0090] The glazing according to the invention comprises a single glass sheet.
[0091] The glazing 10 separates the interior space 4 of the vehicle from the exterior 5 and can be Figure 1 The bend is shown in .
[0092] The glass sheets are preferably 1 mm to 8 mm thick, in particular 1 mm to 4 mm thick. In order to reduce weight, the individual glass sheets should achieve the best possible compromise between low thickness and high safety, in particular when the glazing is installed in a motor vehicle. Such a compromise can be achieved in particular with tempered glass sheets having a thickness of 1.5 mm to 3.1 mm, for example 2.1 mm.
[0093] According to the invention, the outer surface of the glass sheet 1 is preferably bare, while a stack 2 of selective infrared reflecting layers is deposited on the inner part of the sheet 1. Such stacks are well known and comprise in particular a combination of layers based on precious metals, in particular layers based on silver, and dielectric materials, generally referred to as interference layers. As is well known, these stacks consist of a series of layers of dielectric materials, such as oxides and / or nitrides, and of metal layers, including layers based on silver, whose "low-e" properties enable them to selectively reflect the so-called solar infrared or near infrared rays, in particular wavelengths from 780 nm to 2000 nm, and in particular by minimizing the light reflection by means of said interference layer or one or more combinations of interference layers, allowing at least a portion of the visible light of the solar spectrum (wavelengths from 380 to 780 nm), and preferably more than 70% or even more than 80%, to pass. Moreover, the presence of such a stack inside the inner sheet contributes to keeping the interior warm in winter.
[0094] In particular, the stacks according to the invention are selected such that their resistance per square is less than 1.5 ohms per square, preferably even less than 1.2 ohms per square, or even less than 1.1 ohms per square. For example, the resistance per square can be measured using a device such as the SRM-14T from NagyMess-systems.
[0095] Such stacks may comprise up to a few dozen layers with a thickness of 1 to 30 nm and are currently deposited using sputtering techniques, typically magnetron-assisted sputtering techniques.
[0096] Preferred multilayers according to the invention comprise two and preferably three or even four silver-based layers.
[0097] Examples of such stacks are described in the previously cited publications WO 2005 / 051858 A1, WO 2013 / 104439 and WO 2013 / 107983.
[0098] According to the invention, the low-E stack is coated with a layer 3 comprising a colorant.
[0099] The additional layer 3 consists of a layer of polymer compounds. Preferably, such polymers may be or contain polymers of the (meth)acrylate type, in particular of the type described in publications WO2018 / 178559, WO2018 / 178547 or WO2018 / 115768, WO2020 / 016527, or even more preferably of the type described in application WO2020 / 016529 as described above.
[0100] According to the invention, the polymer layer 3 may advantageously be obtained from a liquid composition comprising a (meth)acrylate oligomer comprising at least one methacrylate functional group and preferably comprising a plurality of methacrylate functional groups. For example, the liquid composition may advantageously comprise at least one aliphatic urethane-acrylic oligomer, at least one polymerization initiator and a colorant.
[0101] According to the invention, the polymer layer 3 may advantageously be obtained from a liquid composition comprising a (meth)acrylate compound chosen from monomers, oligomers or polymers comprising at least one (meth)acrylate function and preferably several methacrylate functions.
[0102] For example, the liquid composition comprises at least one monomer or oligomer of the preferred multifunctional (meth)acrylate compound, at least one polymerization initiator, and a colorant.
[0103] Advantageously, the colorant is present in the initial composition in an amount ranging from 5% to 70% by weight relative to the total weight of polymer compounds present in the polymer compound layer, preferably from 10% to 60% or even from 20% to 50% by weight relative to said total weight. The polymer layer 3 may also comprise an adhesion promoter for the stack 2 of layers.
[0104] The polymer layer 3 can be deposited on the stack of layers 2 by applying the above-mentioned liquid composition at room temperature, by roller coating, spraying, dipping, curtain coating or spraying, or by spin coating techniques.
[0105] The polymer layer 3 is then cured by drying at a temperature below 200° C., by UV cross-linking, or by electron beam.
[0106] The thickness of the dried and / or cured polymer layer 3 may be from 0.1 to 25 micrometers, typically from 0.5 to 3 micrometers.
[0107] According to one possible embodiment, the polymer layer comprises an adhesion promoter for the stack. Alternatively, the surface of the stack of layers onto which the colored polymer layer is applied may be pretreated with an adhesion promoter.
[0108] According to the present invention, the polymer layer acts as a matrix for the dye (or colorant), which is specifically selected for its light absorption qualities in the visible light range (380-780 nm) and is also substantially transparent to infrared rays, especially those from 780 to 2000 nm.
[0109] Absorbing visible light means that the dye absorbs most of the visible light between 380 and 780 nm, such as at least 60% or even greater than 70% or greater than 75%, or even substantially all of the visible light between 380 and 780 nm. Similarly, infrared transparent means that the dye allows most, such as at least 60%, preferably at least 70%, or even more than 80%, or even more than 90%, or even substantially all of the infrared light, especially between 780 nm and 2000 nm.
[0110] According to an advantageous embodiment, such a colorant is from Epolight sold by the company Epolin. series of compounds, in particular Epolight compounds 7527B and 7527C (https: / / www.epolin.com / epolight-voirt-dyes-for-solvent-based-systems / ).
[0111] Figure 2 The absorption spectrum of Epolight 7527C at a concentration of 1% by weight in an acrylate layer is shown as an example. The absorbance measured between 380 and 780 nm is 0.79, and the absorbance measured between 780 and 2000 nm is 0.08.
[0112] According to another possibility, a dye of the Sudan type may be chosen, in particular Sudan Black B, the structural formula of which is given below:
[0113]
[0114] Of course, the invention is not limited to such compounds, and any dye having a low infrared absorption coefficient between 780 nm and 2000 nm and a high absorption coefficient in the visible range in its matrix can be used according to the invention. Thus, the dyes used are usually black, but dyes can also be used which do not absorb all visible light, but absorb at least 70% or even 80% of the visible light and thus exhibit a slight but dark coloration.
[0115] More specifically, the method of manufacturing a glazing unit comprises the following steps:
[0116] - depositing the infrared reflective stack 2 as described above on the inner surface of the glass sheet 1 by vacuum sputtering technology,
[0117] - if necessary, shaping the glass, such as bending or tempering,
[0118] - on the inner surface of the glass sheet (sheet 1 with stack 2), liquid deposition, in particular by rolling, spraying, dipping, curtain coating or preferably by spraying, of a polymer layer 3 comprising a colorant or a varnish comprising a colorant,
[0119] - Drying and possibly curing of the polymer layer 3, in particular by UV drying and / or curing.
[0120] Used as a monolithic glazing unit, in particular as a glass roof for automobiles, the glazing according to the invention solves the above technical problems due to its special structure. In particular, it provides the following advantages:
[0121] - low cost of the materials used in its composition, since it does not contain the most expensive elements present in existing structures (in particular, no initial body-tinted PVB, no body-tinted glass), and therefore the manufacturing cost is low. In addition, the liquid deposition method used according to the invention is generally inexpensive due to the high line speed, and the dyes used are commercially available and inexpensive;
[0122] - the possibility of adjusting the light transmittance of the glazing by adjusting the mass concentration of the dye in the polymer layer upwards to values of up to 70% of the total weight (dry matter) of said layer;
[0123] - Optimal solar control properties of glazing achieved:
[0124] a) Due to the presence of the following stack on the glass sheet, it reflects the solar infrared but allows most of the radiation in the visible range to pass,
[0125] b) Due to the nature and positioning of the colorant in the glazing: A large part of the infrared part of the solar spectrum is reflected by the stack of layers, and the remaining radiation, which mainly comprises the visible part of said radiation, is then partially absorbed by the layer comprising the colorant, depending on the concentration of the colorant in said layer. The glazing according to the invention therefore has a low TTS value. Since the infrared radiation cannot reach the polymer layer, no additional heating of the glazing and therefore of the vehicle interior occurs.
[0126] Furthermore, on the inside of the glazing, the reflection of light in the visible range is generally low, typically less than 10%, which ensures improved interior comfort by avoiding mirror effects on said inside surface of the glazing, especially at night.
[0127] The stack of selected layers and the dye concentration are advantageously combined to allow a sufficiently large amount of light to pass through, so as to adequately illuminate the interior space and thereby maintain visual comfort and a pleasant feeling. For example, advantageously, the stack of selected layers, when deposited on a clear glass having a thickness of 2.1 mm without any other elements, produces a T as described above. LA glazing unit having a light transmittance of at least 50%, or even at least 60%, or even at least 70%.
[0128] Two exemplary embodiments of the glazing according to the invention are given below:
[0129] A-Manufacturing of a monolithic structure according to the invention:
[0130] Prepare as above combined Figure 1 Sample A of the described structure, whose dimensions are 10×10 cm 2 .
[0131] Sample A was obtained as follows:
[0132] - Using magnetron assisted sputtering technology, the stack of layers is coated by a filing company under the name The first 2.1mm thick clear glass (T L The stack comprises three silver layers and is described in Example 14 of publication WI2005051858. Its resistance per square is 1.0 ohm / square, measured using a device such as SRM-14T from Nagy Mess Systems.
[0133] On the stack of thin layers, a liquid composition having the following composition is deposited:
[0134] A hexafunctional aliphatic acrylate oligomer having a molecular weight of 1450 g / mol (hereinafter referred to as 6-functional acrylate oligomer), sold by Sartomer under the name CN9010EU.
[0135] - a modified polyorganosiloxane comprising various (meth)acrylates having a molecular weight of 6,500 g / mol, sold under the name Byk 3505 by Byk.
[0136] - an adhesion promoter consisting of triacrylate monomers of the acid type sold under the name SR9051 by Sartomer.
[0137] - the photoinitiator sold under the name Speedcure 500 by Lambson.
[0138] The following table shows the different proportions of the four initial ingredients in the initial mixture:
[0139] [Table 1]
[0140] formula Product Name Weight Percent Acrylate oligomer CN9010EU 94 Polysiloxane Byk 3505 0.5 Adhesion promoter SR9051 0.5 Photoinitiator Speedcure 500 5
[0141] The four components, precursors of the initial polymer matrix, were dispersed in methyl ethyl ketone (MEK) used as solvent.
[0142] Prior to the solvent removal step, according to the invention, the above-mentioned Epolight 7527C dye was also added to the initial solution.
[0143] According to a first example, a mixture comprising 12 wt % of the precursor mixture and 12 wt % of the dye is produced with 76 wt % of MEK.
[0144] According to a second example, a mixture comprising 12 wt % of the precursor mixture and 5 wt % of the dye is produced with 83 wt % of MEK.
[0145] The resulting liquid composition was filtered through a 0.2 micron diameter PTFE filter and then spin-coated onto a glass substrate until it reached a thickness of 5 microns.
[0146] UV irradiation (UVB dose is approximately 280 mJ / cm 2 The layer thus obtained was cured by drying at a rate of 10 m / min. The thickness of the dry colored layer was approximately 1 μm.
[0147] B- Characterization of the glazing according to the invention:
[0148] The optical characterization of the glazings as described above was carried out using a Lambda 900 spectrophotometer from Perkin Elmer.
[0149] According to ISO9050 (2003) the light factor (T L and R L ).
[0150] Total Solar Transmittance (TTS) is measured according to ISO 13837 using the "A" AM 1.5 convention.
[0151] The emissivity is calculated according to the criteria defined in the international standard NF EN 12898: 2001. For the purposes of the examples given below, emissivities of up to 30% are considered satisfactory and above this value the material can no longer be used satisfactorily as insulating glass.
[0152] Table 2 below shows the main chromaticity data of the glazing according to the invention when the Epolight 7527C dye is used:
[0153] [Table 2]
[0154]
[0155] The coloring layer effectively reduces the light transmittance T L The resulting glazing appears deep blue when viewed from inside the cabin.
[0156] The TTS measured according to ISO 13837 convention A, AM 1.5 is much less than 20%, substantially equal to or even lower than the values obtained with the prior art configurations described previously and applied based on PVB and / or tinted glass.
[0157] For both examples the emissivity is less than 30%.
[0158] According to the invention, it appears that the light transmittance T of the glazing can be easily adjusted by acting on the concentration of the coloring agent. L , total energy transmittance TTS and emissivity ε n .
Claims
1. A monolithic glazing comprising a single transparent glass sheet (1), the glazing comprising the following elements in order from the outer side (5) to the inner side (4) of the glazing: - said single transparent glass sheet (1), a stack (2) of layers reflecting infrared radiation, which is preferably in contact with the inner surface of the transparent glass sheet, - a polymer compound layer (3), the polymer layer containing a colorant that absorbs light in the visible range of 380 to 780 nm and is substantially transparent to infrared radiation with a wavelength of 780 to 2000 nm, the polymer layer being in direct contact with the external environment.
2. The monolithic glazing according to claim 1 , wherein the absorbance of the dye between 780 nm and 2000 nm measured at a concentration of 1% by weight in a 40 micron layer of a (meth)acrylate polymer on the absorption spectrum between 380 and 2000 nm by a Perkin-Elmer lambda 950 spectrophotometer is at most one third of the absorbance between 380 nm and 780 nm. 3 . The glazing according to claim 1 , wherein the average molar extinction coefficient of the dye between 780 nm and 2000 nm at 25° C. is at most one third the average molar extinction coefficient between 380 nm and 780 nm.
4. The monolithic glazing according to claim 1 , wherein the stack of layers reflecting infrared radiation is a stack of at least two, and preferably at least three, functional layers based on silver, separated by layers of dielectric material, in particular layers of oxides or nitrides.
5. The glazing according to claim 1, wherein the polymer layer (3) comprises or preferably consists of a polymeric compound selected from (meth)acrylate compounds, which are preferably multifunctional and contain at least two acrylate functional groups.
6. The glazing according to claim 1 , wherein the polymer layer ( 3 ) is obtained by crosslinking a polymerizable composition comprising a (meth)acrylate compound, optionally a polyorganosiloxane group, optionally a polymerization initiator, optionally an adhesion promoter to the stack, the (meth)acrylate compound comprising and preferably being a high-functionality (meth)acrylate compound: - has at least four (meth)acrylate functional groups and accounts for at least 65% by weight relative to the total weight of the organic protective layer, or - has at least five (meth)acrylate functional groups and accounts for at least 50% by weight relative to the total weight of the organic protective layer.
7. The monolithic glazing according to claim 1, wherein the polymer layer (3) has a thickness of 0.1 to 25 micrometers, in particular 0.2 to 10 micrometers, particularly preferably 0.5 to 3 micrometers.
8. The glazing according to claim 1, wherein the coloring agent is selected from the group consisting of Epolight sold by the company Epolin. Compounds in the series, in particular compounds 7527B and Epolight 7527C.
9. The monolithic glazing according to claims 1 to 7, wherein the colorant is selected from Sudan Black (CAS4197-25-5) or Nigrosine Solvent black 5 (CAS11099-03-9), and Sudan Black is preferred 10 . The glazing according to claim 1 , wherein the colorant represents 5 to 70% by weight of the polymer layer, preferably 20 to 50% by weight of the polymer layer.
11. The monolithic glazing according to claim 1, characterized in that The glass sheet has a thickness of 0.7 to 5 mm, preferably 1.6 to 3.1 mm.
12. Use of a monolithic glazing according to one of the preceding claims as a roof window, side window or rear window of a motor vehicle.
